Characterisation of iron oxide encrusted microbial fossils - Levett, Alan (Sci Rep, 2020)
Robust methods for the characterisation of microbial biosignatures in geological matrices is critical for developing mineralogical biosignatures. Studying microbial fossils is fundamental for our understanding of the role microorganisms have played in elemental cycling in modern and ancient environments on Earth and potentially Mars. Here, we aim to understand what promotes the fossilisation of microorganisms after the initial stages of biomineralisation, committing bacteriomorphic structures to the geological record within iron-rich environments. Mineral encrusted cell envelope structures were routinely identified within a goethite-rich vein that cross-cut the saprolite (iron ore) of a weathered banded iron formation (BIF) system in the Quadrilátero Ferrífero, Brazil. The preservation of potential organic and mineralogical biosignatures associated with these fossils was characterised using the following high-resolution analytical techniques: scanning and transmission electron microscopy, focused ion beam scanning electron microscopy, nanoscale secondary ion mass spectrometry, synchrotron-based Fourier transform infrared spectroscopy and Raman spectroscopy. Electron microscopy demonstrated that mineral nucleation associated with a range of cell envelope structures typically followed the extant cell templates. These biologically-influenced iron-rich minerals are microcrystalline with minimal secondary growth. In contrast, intracellular mineralisation formed larger minerals that grew inward from the cell membrane to infill intracellular voids after cell death. A three dimensional reconstruction of encrusted cell envelopes in a fossilised biofilm suggests that microorganisms may be able to replicate, during the initial stages of mineralisation. Carbon and nitrogen signatures are preserved associated with the cell envelope structures; however, there were no conclusive mineralogical biosignatures associated with the mineralised cell envelopes highlighting the classical importance of morphology and elemental biosignatures in determining the biogenicity of bacteriomorphic structures.